Religion and Public Administration. An Introduction Edoardo Ongaro, Michele Tantardini Edward Elgar Publishing - Călin Emilian Hințea (Transylvanian Review of Administrative Sciences, 2023)
Edoardo Ongaro and Michele Tantardini’s book titled Religion and Public Administration. An Introduction is an original approach to understanding the relationship between religion and public administration in an effort to analyze the ‘elephant in the room’ (p. 1) of administration studies. The authors’ understanding of religion broadly refers to people’s relationship with divinity. It seeks to define a global perspective that attempts to ‘conceptualize and theorize the influence of religion in the functioning of public administration systems in all regions of the globe’ (p. 3). Their study is intended as an introductory essay for those interested in this topic, an essay that considers the contextual data in which administrative systems operate.